The Difficulty in Writing Insya' Weekely Program and Its Solution Given by the Teacher in Ponpes Muharrikun Najah Klaten / صعوبات كتابة الإنشاء الأسبوعي وحلّ المعلّم عليها بمعهد محرّك النّجاح بكلاتين - Fadhilah, Rif'atul (UIN Raden Mas Said Surakarta, 2021)
This study aims to describe the difficulty of students in writing Insya' Usbu'i. The method of the study is a descriptive qualitative method, while the research subject is santriwati, and the data source in this study is the director of the institute and the supervisor. The data collection techniques used in this study are interviews, observations, and documents. The result of this study can be known that: 1) the difficulty of students in insya' includes the lack of vocabulary that students have and the low understanding of students to nahwu Sharaf; 2) composing sentences include difficulty in choosing vocabulary, syntax, and morphological grammar accuracy, 2) The first language of the students still dominates so that interest in Arabic is still lacking; 3) the efforts of teachers to improve students' ability to write Insha' is to give notes one by one of the students' work and explain each mistake.